Comparative investigation of atopic dermatitis with inflammatory skin rashes in traditional Iranian medicine references - Abbasi, Shirin; Shams, SeyedMohammad; Kamalinejad, Mohammad (Advances in Nursing & Midwifery, 2017)
Abstract: Background and Aim: Atopic Dermatitis (AD) or innate eczema is the most common chronic relapsing inflammatory skin diseases in infantile and childhood, which is rarely continued into adulthood. Family or personal history of atopy (e.g. asthma, allergic rhinitis or food sensitivity) is very common in children suffered from AD. Materials and Methods: Although the role of inflammatory processes in AD is well recognized, the exact pathogenesis of it is not fully understood. Therefore, comparison between AD and diseases described in traditional Iranian medicine (TIM) as a holistic medicine may open new horizons to the deeper comprehension and therapeutic approaches. In this study, we try to draw an analogy between AD and inflammatory skin rashes described in traditional Iranian medicine references. The lack of information of lesion's location, being chronic or recurrent and family or personal history of allergy in traditional Iranian medicine references led us to solely use the clinical manifestation. Hence, according to the major symptoms of AD, inflammatory rashes, pruritus, and xerosis are defined as the clinical manifestation of AD in this study. At the first step, we compare the symptoms and causes of inflammation skin rashes in traditional medicine and clinical manifestation with pathogenesis of AD in modern medicine. In the second step, we extract the similarities and differences between AD and inflammatory skin rashes described in TIM. Conclusion: The results reveal that, Namleh and Javarsiyeh have the most common symptoms to AD, among all diseases described in traditional Iranian medicine. Key words: Dermatitis, Atopic; Inflammation; Medicine, Traditional